Dissecting the Evolving Risk of Relapse over Time in Surveillance for Testicular Cancer. (19th February 2018) - Nayan, Madhur; Hamilton, Robert J.
Abstract : Testicular cancer is the most common malignancy in young men, and the incidence is increasing in most countries worldwide. The vast majority of patients present with clinical stage I disease, and surveillance is being increasingly adopted as the preferred management strategy. At the time of diagnosis, patients on surveillance are often counselled about their risk of relapse based on risk factors present at diagnosis, but this risk estimate becomes less informative in patients that have survived a period of time without experiencing relapse. Conditional survival estimates, on the other hand, provide information on a patient's evolving risk of relapse over time. In this review, we describe the concept of conditional survival and its applications for surveillance of clinical stage I seminoma and nonseminoma germ cell tumours. These estimates can be used to tailor surveillance protocols based on future risk of relapse within risk subgroups of seminoma and nonseminoma, which may reduce the burden of follow-up for some patients, physicians, and the health care system. Furthermore, conditional survival estimates provide patients with a meaningful, evolving risk estimate and may be helpful to reassure patients and reduce potential anxiety of being on surveillance.